Protective and anti-arrhythmic effects of dauricine and verapamil on acute myocardial infarction in anesthetized dogs - Zhu Jie-Quan; Zeng Fan-Dian; Hu Chong-Jia (Acta Pharmacologica Sinica; Vol 13, No 3 (May 1992): Acta Pharmacologica Sinica, 2016)
Dauricine (Dau) 5 mg.kg-1 and verapamil (Ver) 0.15 mg.kg-1 iv followed by infusions of 0.1 and 0.01 mg.kg-1.min-1, respectively, for 30 min, depressed the elevated coronary venous blood LDH and CPK after LAD occlusion. Dau produced antagonistic effects on acute myocardial ischemia-induced ventricular ectopic activities (VE) and ventricular tachycardia (VT). The incidences of VE and VT in Ver group and ventricular fibrillation (VF) in both groups tended to descend. The results suggested that Dau and Ver produced marked protective effects on myocardial infarction and antagonized the acute ischemic arrhythmia.